THE CORRELATION OF JOINT SPACE WIDTH WITH SYNOVIAL FLUID CARTILAGE OLIGOMERIC MATRIX PROTEIN LEVEL IN KNEE OSTEOARTHRITIS PATIENTS - Sa'diyah, Halimah; Faridin HP, (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
Osteoarthritis (OA) was a degenerative joint disease associated with joint cartilage damage, where the most commonly affected joints are vertebrae, pelvis, knee, and ankle. Pathomechanism of OA includes various etiologies that play a role in the balance destruction and synthesis of cartilage. Radiology examination was the most common method used to monitor the progression of OA but can not show changes in knee OA except in the advanced phase of the disease. Conventional radiology can estimate the thickness of the cartilage through measurement joint space width (JSW). One alternative method that can detect changes in the joint at an early stage of the disease is a measurement of the synthesis and degradation markers of the tissue. Cartilage oligomeric matrix protein (COMP) was one of the cartilage destruction markers of non-aggrecan and non-collagen groups, found in cartilage and other tissues. Several studies have reported the correlation between serum or synovial fluid COMP level with the radiographic progression of knee OA patients. This study aimed to assess the correlation between joint space width and synovial fluid COMP level in knee OA subjects. The study was a descriptive-analytic method with a cross-sectional design in 69 knee OA subjects. It was conducted in the rheumatology outpatient clinic of Wahidin Sudirohusodo Hospital Makassar and its networks on March-June 2015. In this study, we found a correlation between joint space width (JSW) and synovial fluid COMP level, where synovial fluid COMP levels were higher in knee OA subjects with more severe joint space width narrowing, and it was not influenced by age and obesity